Antibacterial, anticancer and antioxidant potential of silver nanoparticles engineered using Trigonella foenum-graecum seed extract - Goyal, Shivangi; Gupta, Nidhi; Kumar, Ajeet; Chatterjee, Sreemoyee; Nimesh, Surendra (IET nanobiotechnology, 2018)
In this study, the authors report a simple and eco-friendly method for the synthesis of silver nanoparticles (AgNPs) using Trigonella foenum-graecum (TFG) seed extract. They explored several parameters dictating the biosynthesis of TFG-AgNPs such as reaction time, temperature, concentration of AgNO3, and TFG extract amount. Physicochemical characterisation of TFG-AgNPs was done on dynamic light scattering (DLS), field emission electron microscopy, energy dispersive X-ray spectroscopy, X-ray diffraction and Fourier transform infrared spectroscopy. The size determination studies using DLS revealed of TFG-AgNPs size between 95 and 110 nm. The antibacterial activity was studied against Escherichia coli, Proteus vulgaris, Pseudomonas aeruginosa and Staphylococcus aureus. The biosynthesised TFG-AgNPs showed remarkable anticancer efficacy against skin cancer cell line, A431 and also exhibited significant antioxidant efficacy.